2022
DOI: 10.2147/dddt.s349678
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Exerts Pharmacological Effects Through Multiple Signaling Pathways: A Comprehensive Review

Abstract: As The main effective monomer of the traditional Chinese medicine Sophora flavescens Ait , matrine has a broad scope of pharmacological activities such as anti-tumor, anti-inflammatory, analgesic, anti-fibrotic, anti-viral, anti-arrhythmia, and improving immune function. These actions explain its therapeutic effects in various types of tumors, cardiopathy, encephalomyelitis, allergic asthma, rheumatoid arthritis (RA), osteoporosis, and central nervous system (CNS) inflammation. Evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 147 publications
(180 reference statements)
0
21
0
Order By: Relevance
“…Its main component, Sophora flavescens, has many effects, including antibacterial and anti-inflammatory, insecticidal and anti-pruritic, anti-viral, and analgesic (He et al, 2015). Many studies have confirmed that the pharmacological mechanism of sophora flavescens may be via the activation or suppression of key molecules in certain cellular signaling pathways, such as nuclear factor kappa B (NF-kB), phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) and transforming growth factor-b/mothers against decapentaplegic homolog (TGF-b/Smad) (Lin et al, 2022;Tang et al, 2022). Furthermore, other herbs in the formula also have certain bactericidal and antiinflammatory effects, which complement each other.…”
Section: Discussionmentioning
confidence: 99%
“…Its main component, Sophora flavescens, has many effects, including antibacterial and anti-inflammatory, insecticidal and anti-pruritic, anti-viral, and analgesic (He et al, 2015). Many studies have confirmed that the pharmacological mechanism of sophora flavescens may be via the activation or suppression of key molecules in certain cellular signaling pathways, such as nuclear factor kappa B (NF-kB), phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) and transforming growth factor-b/mothers against decapentaplegic homolog (TGF-b/Smad) (Lin et al, 2022;Tang et al, 2022). Furthermore, other herbs in the formula also have certain bactericidal and antiinflammatory effects, which complement each other.…”
Section: Discussionmentioning
confidence: 99%
“…When the cell is stimulated, IKK promotes the phosphorylation of IκB and leads to the dissociation of NF-κB. Then, NF-κB is translocated into the nucleus and binds to DNA, resulting in gene transcription and protein synthesis, which are related to inflammation response [126,127]. Nearly all the anti-inflammatory functions of TCMs listed here are related to the NF-κB pathway (Figure 3).…”
Section: Mechanism Of Chinese Medicine In Treating Fungal Infectious ...mentioning
confidence: 98%
“…Nearly all the anti-inflammatory functions of TCMs listed here are related to the NF-κB pathway (Figure 3). MAPK cascades mediate the signal transduction from extracellular signals to intracellular reactions [126]. There are at least three MAPK cascade signal transduction pathways that are involved in the anti-inflammation effects of TCM ingredients: ERK, JNK, and p38.…”
Section: Mechanism Of Chinese Medicine In Treating Fungal Infectious ...mentioning
confidence: 99%
“…Matrine (MAT), a tetracyclo quinolizine alkaloid, is the main active ingredient extracted from the dry root of Sophora flavescens and used in a variety of CNS and peripheral inflammatory diseases [ 184 ]. Intraperitoneal MAT injection effectively inhibited EAE progression and significantly reduced oligodendrocyte apoptosis, microglial activation, and inflammatory factor secretion.…”
Section: Natural Compounds Against Oxidative Stress In Animal Models ...mentioning
confidence: 99%